The Role of Husbands in Teaching Hinduism to Sudhi Wadani Wife in Interfaith Marriages - Ratini, Ni Ketut (Jayapangus Press, 2025)
Interfaith marriage in Indonesia is a complex issue that involves legal, social, and religious dilemmas. Marriages must be legal under both religious and state law, which requires the bride and groom to be of the same faith to be recognized as religiously valid. This provision has caused controversy and injustice, especially regarding religious freedom and human rights in a multicultural society. The Study aims to focuses on the role of husbands in providing an understanding of Hinduism to wives who have undergone Sudhi Wadani who previously adhered to other religions, especially in the context of interfaith marriages. This research uses a qualitative, phenomenological method, in-depth interview techniques, and participatory observation. was conducted in Palu City in 2024 with 13 informants husband. The results showed that the husband plays a central role in guiding his wife to understand the teachings of Hinduism, which is realized through direct teaching, accompanying in religious activities, and being a role model. The obstacles husbands face include limited religious knowledge, lack of time due to busy work, and wife's sensitivity. The strategies husbands apply to overcome these obstacles include inviting wives indirectly to engage in religious activities, patient communication, and utilization of religious communities to learn. This concludes that the husband's role in guiding his wife to understand the teachings of Hinduism in an interfaith marriage is vital and requires consistent, flexible, and practice-based efforts. Practical recommendations for interfaith couples and relevant institutions to strengthen support for Hindu husbands of wives who have undergone Sudhi Wadani in interfaith marriages.